EXAMINING THE IMPACT OF MULTIMEDIA PRESENTATION ON MANDARIN LANGUAGE LEARNERS - NORFATIHAH AMANDA, ABDULLAH (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examines the impact of multimedia presentation of Image-Narration (IN) and Image- Narration- On-screen text (INT) on Mandarin language learners to see which multimedia presentation aids in learning and teaching as well as to see if the gender stigma of females’ verbal abilities can be generalised to Mandarin language learning. 40 undergraduate students (20 male and 20 females) participated in this study and they were non-native speakers. Participants were given a personalised link to go through Study Phase and Test Phase. The initial plan was to collect the data by conducting a normal experimental manipulation but since the data collection was carried out during the period of Movement Control Order (MCO), therefore Google Form was used with a Timify add-on from Google to ensure control on the design aspects of experiments. Participants were given a personalized link that only they can access via email address and will be brief about the experiment through Whatsapp. They were permitted to withdraw from the experimentation at any time and were given another link to answer 20 questions of the Mandarin language and if they score 3 and below then they will be selected for the next phase. Next, the selected participants will be assigned randomly to the IN or INT group. After learning the mandarin language via the respective multimedia presentations, participants were given the previous 10 basic questions with another 10 extra phrases (that are taught via video uploaded to Youtube) to measure their retention on mandarin vocabulary. A two-way independent ANOVA was conducted on the experimental data and the findings revealed that there was no significant effect between the types of multimedia presentation used and also gender does not affect an individuals’ learning capabilities hence no significant effect was found in gender. This finding offers an ambitious view to provide students and teachers with increased knowledge of elective approaches for studying and displaying foreign languages (e.g. Mandarin) that can improve and strengthen memory consolidation of acquired vocabulary.